Instagram As A Platform For Akhlakul Karimah - Rahmat Lutfi Guefara (International Journal of Islamic Educational Research, 2024)
Akhlak degradation or moral degradation is at the foundation of a variety of problems and social issues in society during one's life. Moral degradation develops as a result of entering digital spaces, as shown by the presence of Instagram as a digital social media. As a result, discovering a solution to this problem becomes a priority. This study aims to provide a solution to the phenomenon of moral degradation in Instagram by exploring the concept of morality based on Sufism values, by determining the formulation of the problem including a description of moral degradation in Instagram, Sufism and morality in Islam, and the concept of akhlakul karimah based on sufism values. This study uses a qualitative approach with descriptive methods, as well as literature study as a data collection technique. The findings of this study explain the phenomena of moral degradation on Instagram, which generates a whole slew of issues. Furthermore, this research explains Sufism and morality in Islam, as well as their integration in the concept of morality based on Sufism values through various exercises and efforts as a resolution to moral degradation on the social media platform Instagram.